Crosstalk between Biomolecular Condensates and Proteostasis - Emmanuel Amzallag; Eran Hornstein (Cells, 2022)
Proper homeostasis of the proteome, referred to as proteostasis, is maintained by chaperone-dependent refolding of misfolded proteins and by protein degradation via the ubiquitin-proteasome system and the autophagic machinery. This review will discuss a crosstalk between biomolecular condensates and proteostasis, whereby the crowding of proteostasis factors into macromolecular assemblies is often established by phase separation of membraneless biomolecular condensates. Specifically, ubiquitin and other posttranslational modifications come into play as agents of phase separation, essential for the formation of condensates and for ubiquitin-proteasome system activity. Furthermore, an intriguing connection associates malfunction of the same pathways to the accumulation of misfolded and ubiquitinated proteins in aberrant condensates, the formation of protein aggregates, and finally, to the pathogenesis of neurodegenerative diseases. The crosstalk between biomolecular condensates and proteostasis is an emerging theme in cellular and disease biology and further studies will focus on delineating specific molecular pathways involved in the pathogenesis of amyotrophic lateral sclerosis (ALS) and other neurodegenerative diseases.